The physical universe / Konrad B Krauskopf, Arthur Beiser - Krauskopf, Konrad B.
Accompanied by a strong media component with the Connect online homework system, 'CPS' eInstruction student response system questions, and PowerPoint lectures, this title shows students how science works, how scientists approach problems, and why science constantly evolves in its search for understanding.